2014
DOI: 10.1111/aogs.12532
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of self‐reported smoking cessation during pregnancy

Abstract: Evidence of bias of self-reported smoking cessation during pregnancy is reported in high-income countries but not elsewhere. We sought to evaluate self-reported smoking cessation during pregnancy using biochemical verification and to compare characteristics of women with and without biochemically confirmed cessation in Argentina and Uruguay. In a cross-sectional study from October 2011 to May 2012, women who attended one of 21 prenatal clinics and delivered at selected hospitals in Buenos Aires, Argentina and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 11 publications
(16 reference statements)
0
25
0
1
Order By: Relevance
“…Tong et al. reported that 10% of woman who claimed to have stopped smoking showed biochemical evidence of continued smoking 24 . It is possible that we overestimated the risk of RWG in the ex-smoker group, and that smoking cessation during pregnancy may have a greater effect on RWG in early infancy than the study results indicate.…”
Section: Discussionmentioning
confidence: 58%
“…Tong et al. reported that 10% of woman who claimed to have stopped smoking showed biochemical evidence of continued smoking 24 . It is possible that we overestimated the risk of RWG in the ex-smoker group, and that smoking cessation during pregnancy may have a greater effect on RWG in early infancy than the study results indicate.…”
Section: Discussionmentioning
confidence: 58%
“…About 10.0% of women who self-reported smoking cessation during pregnancy had biochemical evidence of continued smoking; detailed results are published elsewhere. 22 …”
Section: Methodsmentioning
confidence: 99%
“…This may be even more pronounced during pregnancy, and in this study smokers also claimed to be non-smokers. The overestimation has been described before (25).…”
Section: Conflicts Of Interestmentioning
confidence: 75%